2017
DOI: 10.1002/2016ja023839
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude GPS phase scintillation from E region electron density gradients during the 20–21 December 2015 geomagnetic storm

Abstract: A novel operating mode for Poker Flat Incoherent Scatter Radar (PFISR) has been developed to support the study of GPS L1 scintillations arising from electron density gradients over Alaska. Previous authors have combined GPS scintillation data with either PFISR or multispectral imagery in this region. This analysis combines all three techniques to determine both gradient parameters as well as the most likely ionospheric source, including a conjunction analysis between GPS signals and known PFISR beams. This app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…The association of auroral phenomena and GNSS signal disturbances has been established in a variety of studies (e.g., Datta‐Barua et al, ; Jin et al, , ; Kinrade et al, ; Loucks et al, ; Prikryl et al, ; Smith et al, ). The presumption has been that phase scintillations are caused by density irregularities with k ⊥ dimension similar to the radius of the first Fresnel zone (∼270 m for the L 1 signal at E region distances) (Kintner et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of auroral phenomena and GNSS signal disturbances has been established in a variety of studies (e.g., Datta‐Barua et al, ; Jin et al, , ; Kinrade et al, ; Loucks et al, ; Prikryl et al, ; Smith et al, ). The presumption has been that phase scintillations are caused by density irregularities with k ⊥ dimension similar to the radius of the first Fresnel zone (∼270 m for the L 1 signal at E region distances) (Kintner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A steep density gradient across a moving auroral boundary can also produce arbitrary phase transients (Chartier et al, 2016). These boundary regions are also sites of instability formation, leading to a causative connection with irregularity formation (Loucks et al, 2017) and a potential mixture of sources for high-frequency phase variations on an intersecting GPS link (Chartier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work (Su, ) examined a number of scintillations, at least one of which was attributed to the F layer (Datta‐Barua et al, ; Su, Datta‐Barua, et al, ). More recently, individual case studies (Loucks et al, ; Semeter et al, ) showed the possibility that E layer irregularities, particularly related to auroral activity, were correlated with GPS‐effective scintillations. With a statistical study of 17 days over two Antarctic winters, Kinrade et al () showed phase scintillations to be more correlated with auroral 557.7‐nm emissions (which tend to be E layer) than 630.0‐nm emissions (throughout the F layer).…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with formation of scintillation‐causing irregularities in plasma gradients at the arc edges. This suggests that spatial variations (gradients) of IPP brightness correlate positively with scintillation effects observed on a GPS satellite signal (Forte et al, ; Haerendel et al, ; Loucks et al, ; Noel et al, ; Uritsky et al, ). It is also noted that low‐level fluctuations (blue, σ φ 0.2–0.4) are more probable when the IPP is inside the arc by ~10%.…”
Section: Analysis and Resultsmentioning
confidence: 95%
“…Understanding aurora in terms of impact on GPS signals is important as it provides information to help predict and mitigate scintillation effects due to space weather. Many studies (e.g., Jin et al, ; Kinrade et al, , ; Loucks et al, ; Prikryl et al, ; Semeter et al, ; Van der Meeren et al, ) have shown a positive correlation between GPS phase scintillations and auroral structures. The magnitude of the phase scintillation was determined to be related to the level of brightness of the aurora.…”
Section: Introductionmentioning
confidence: 99%